2017
DOI: 10.3389/fmicb.2017.01825
|View full text |Cite
|
Sign up to set email alerts
|

Sixty Years (1957–2017) of Research on Toxoplasmosis in China—An Overview

Abstract: Toxoplasma gondii is a ubiquitous zoonotic pathogen belonging to apicomplexan parasites. Infection in humans and animals may cause abortion and other severe symptoms under certain circumstances, leading to great economical losses and public health problems. T. gondii was first discovered in China in 1955 and the corresponding work was published in 1957. Since then, a lot of work has been done on this parasite and the diseases it causes. This review summarizes the major progress made by Chinese scientists over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 159 publications
(102 reference statements)
4
44
0
Order By: Relevance
“…This finding indicates that T. gondii oocysts are widely distributed in the country. This viewpoint was also verified by other reports ( Pan et al, 2017 ; Yang et al, 2017a ). Furthermore, the popularity of hotpot with undercooked mutton and pork increases the risk of human T. gondii infection in China, with other food animals also remaining as threats to public health ( Guo et al, 2015 ; Yang et al, 2017b ).…”
Section: T Gondii Prevalence and Risk Assessment In Food Ansupporting
confidence: 90%
See 1 more Smart Citation
“…This finding indicates that T. gondii oocysts are widely distributed in the country. This viewpoint was also verified by other reports ( Pan et al, 2017 ; Yang et al, 2017a ). Furthermore, the popularity of hotpot with undercooked mutton and pork increases the risk of human T. gondii infection in China, with other food animals also remaining as threats to public health ( Guo et al, 2015 ; Yang et al, 2017b ).…”
Section: T Gondii Prevalence and Risk Assessment In Food Ansupporting
confidence: 90%
“…Approximately 0.3% of pregnant women have been diagnosed with an acute infected of T. gondii during pregnancy (1990–2010) ( Gao et al, 2012 ). Pan et al (2017) have shown that the prevalence of animal T. gondii infections in sheep, swines, and chickens in China from 2010 to 2017 is significantly higher than that in humans. Most reports about T. gondii from China have been published in local journals, which are generally inaccessible to readers around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Not all playgrounds, including sandboxes, are protected against cats, especially since these animals are active at nig ht. 3,4,7,30,31,33,36,40,51,[102][103][104][105] The risks to children is amplified due to their geophagy, and frequent face touching especially around the mouth and nose. Also, due to their small posture, children are exposed to airborne forms of invasive parasites which rise up with the dust.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that one-third of the world's population is infected by this parasite, with more than 2 million people affected every year in the European region. In addition, T. gondii can infect more than 200 warmblooded animal species causing toxoplasmosis in them (115,116). According to WHO, it is estimated that 95 % of people with an immunocompetent system will not develop clinical symptoms when they are infected with T. gondii, or they may experience mild influenza--like symptoms such as fever, headache or myalgia that quickly pass (116).…”
Section: Antitoxoplasmosis Activitymentioning
confidence: 99%
“…Tachyzoites can be detected in the host's leukocytes or in the bloodstream where they circulate freely. These tachyzoites localize in brain, liver and muscle tissue and develop into bradyzoite tissue cysts (115,118,119).…”
Section: Antitoxoplasmosis Activitymentioning
confidence: 99%